Lipid Profile as a Nutritional Status Marker in Tuberculosis - Vaishnavi Sandip Salunkhe; Vinayak Wamanrao Patil; Pooja Rai (Journal of Clinical and Diagnostic Research, 2020)
Introduction: Tuberculosis (TB) is a global health problem. India has the highest cases in the world and accounts for nearly one fifth of global cases. TB is a chronic disease and in long term leads to malnutrition. Lipids are important constituents in the body that determine the nutritional status and immune function. Aim: To study lipid profile as a nutritional status marker in pulmonary TB. Materials and Methods: Fifty patients of pulmonary TB and fifty healthy subjects in age group of 18-60 years were included for study. The lipid profile was analysed to assess the nutritional status of the patients. Unpaired t-test was used to study the significance of study parameters in cases and controls group. The p-value of <0.05 was considered to be statistically significant. Results: Out of 100 subjects 63% were males 37% were females. Significant decreased levels of total cholesterol, Triglycerides, High Density Lipoprotein-Cholesterol (HDL), Very Low Density Lipoprotein-Cholesterol (VLDL), Low Density LipoproteinCholesterol (LDL) were seen in cases as compared to controls. Conclusion: In this study, it was observed that lipid profile could play a significant role as a biochemical marker of nutritional status in pulmonary TB patients. Thus, knowledge of these levels can help in providing a proper balanced diet to these patients which can ultimately help in better quality treatment.